Step-growth polymers from cashew nut shell liquid (CNSL)-based aromatic difunctional monomers - Chatterjee, Deepshikha; Sadavarte, Nilakshi V.; Shingte, Rahul D.; More, Arvind S.; Tawade, Bhausaheb V.; Kulkarni, Arun D.; Ichake, Amol B.; Avadhani, C. V.; Wadgaonkar, Prakash P. (Cashew Nut Shell Liquid, 2017)
Cashew nut shell liquid (CNSL) is an attractive renewable resource material which is available in abundance (44,50,000 tonnes worldwide and 7,53,000 tonnes in India in 2013) at low cost (around 0.27 $/kg in 2015) and is mainly composed of anacardic acid, cardanol, cardol and 2-methyl cardol. Cardanol is obtained as a major product during hot oil extraction or roasting process of CNSL. Cardanol possesses interesting structural features. The aromatic ring of cardanol can undergo electrophilic substitution reactions; the unsaturated side chain can undergo epoxidation, hydrogenation, metathesis, etc., while the phenolic hydroxyl group can undergo various reactions such as esterification and alkylation. Such opportunities of chemical modifications offered by cardanol have been extensively explored to synthesise a range of interesting aromatic difunctional monomers that have subsequently been utilised to prepare a host of step-growth polymers. Summarised herein are research efforts that have contributed towards the synthesis of step-growth polymers based on aromatic difunctional monomers derived from cardanol. The properties of high-performance polymers, with a particular focus on processability and thermal characteristics, are highlighted.

Synthesis and characterization of partially bio-based polyimides based on biphenylene-containing diisocyanate derived from vanillic acid - Kuhire, Sachin S.; Ichake, Amol B.; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (European Polymer JOurnal, 2018)
A new bio-based biphenylene-containing diisocyanate, namely, 5,5'-diisocyanato-2,2',3,3'-tetramethoxy-1,1'-biphenyl (BDI) was synthesized starting from vanillic acid - a lignin-derived phenolic acid. A series of new partially bio-based polyimides was prepared by polycondensation of BDI with five commercially available aromatic dianhydrides. Polyimides exhibited good solubility in organic solvents and medium molecular weights (Mn (GPC, polystyrene standard) = 25,100-32,200 g mol(-1)). Polyimides showed good thermal stability with 10% degradation temperature and glass transition temperature in the range 459-473 degrees C and 262-329 degrees C, respectively.

Aromatic polycarbonates bearing pendant maleimide groups via functional monomer approach: synthesis and characterization - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Rajamohanan, P. R.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2019)
A new bisphenol containing pendant maleimide group, viz., 4, 4'-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA), was synthesized starting from commercially available 4, 4'-bis (4-hydroxyphenyl) pentanoic acid. Aromatic (co)polycarbonates possessing pendant maleimide groups were synthesized by solution polycondensation of BPA-MA or varying mixtures of BPA-MA and bisphenol-A (BPA) with triphosgene in dry dichloromethane in the presence of triethylamine as a base. Inherent viscosities and number average molecular weights of (co)polycarbonates were in the range 0.46-0.66 dL/g and 24,600-36,700, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polycarbonates. (Co)polycarbonates were characterized using FT-IR, H-1 NMR, C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolycarbonate containing pendant maleimide groups was carried out quantitatively using thiol-maleimide Michael addition reaction with two thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol. Additionally, it was demonstrated that copolycarbonate containing pendant maleimide groups could be used to form insoluble cross-linked gel by reaction with a multifunctional thiol cross-linker, namely, pentaerythritol tetrakis(3-mercaptopropionate).
Keywords: Aromatic polycarbonate; Cross-linking; maleimide group; Thiol-maleimide reaction; Triphosgene

New approach for the synthesis of miktoarm star polymers through a combination of thiol-epoxy ``click'' chemistry and ATRP/Ring-opening polymerization techniques - Gadwal, Ikhlas; Wadgaonkar, Prakash P.; Ichake, Amol B.; Mane, Shivshankar R. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
A new approach was developed for synthesis of certain A(3)B(3)-type of double hydrophilic or amphiphilic miktoarm star polymers using a combination of ``grafting onto'' and ``grafting from'' methods. To achieve the synthesis of desired miktoarm star polymers, acetyl protected poly(ethylene glycol) (PEG) thiols (M-n = 550 and 2000 g mol(-1)) were utilized to generate A(3)-type of homoarm star polymers through an in situ protective group removal and a subsequent thiol-epoxy ``click'' reaction with a tris-epoxide core viz. 1,1,1-tris(4-hydroxyphenyl)ethane triglycidyl ether. The secondary hydroxyl groups generated adjacent to the core upon the thiol-epoxy reaction were esterified with alpha-bromoisobutyryl bromide to install atom transfer radical polymerization (ATRP) initiating sites. ATRP of N-isopropylacrylamide (NIPAM) using the three-arm star PEG polymer fitted with ATRP initiating sites adjacent to the core afforded A(3)B(3)-type of double hydrophilic (PEG)(3)[poly(N-isopropylacrylamide)] (PNIPAM)(3) miktoarm star polymers. Furthermore, the generated hydroxyl groups were directly used as initiator for ring-opening polymerization of epsilon-caprolactone to prepare A(3)B(3)-type of amphiphilic (PEG)(3)[poly(epsilon-caprolactone)](3) miktoarm star polymers. The double hydrophilic (PEG)(3)(PNIPAM)(3) miktoarm star polymers showed lower critical solution temperature around 34 degrees C. The preliminary transmission electron microscopy analysis indicated formation of self-assembly of (PEG)(3)(PNIPAM)(3) miktoarm star polymer in aqueous solution. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 146-156
Keywords: Atom transfer radical polymerization (ATRP); miktoarm star polymers; ring-opening polymerization (ROP); thermoresponsive; thiol-epoxy

Synthesis and characterization of partially biobased aromatic (Co)polycarbonates containing biphenylene units and pendant pentadecyl chains - Ichake, Amol B.; Nagane, Samadhan S.; Jadhav, Uday A.; Torris, Arun; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (Macromolecular Chemistry and Physics, 2022)
2-Pentadecyl-[1,1''-biphenyl]-4,4''-diol (PBD) is synthesized starting from cashew nut shell liquid-a by-product of cashew processing industry. A new series of partially biobased aromatic (co)polycarbonates possessing biphenylene units and pendant pentadecyl chains is synthesized by solution polycondensation of PBD or varying compositions of PBD and bisphenol-A with triphosgene in dry dichloromethane. Inherent viscosities and number average molecular weights of (co)polycarbonates are in the range 0.51-1.24 dL g(-1) and 18 x 10(3)- 43.4 x 10(3) g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. Flexible, transparent, and free-standing films of (co)polycarbonates can be cast from chloroform solution. (Co)polycarbonates are characterized using Fourier transform infrared spectroscopy (FTIR), H-1 NMR, C-13 NMR spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry, and thermogravimetric analysis. T-10 and T-g values of (co)polycarbonates are in the range 417-433 and 8-147 degrees C, respectively. It is demonstrated that the T-g values can be tuned by incorporation of appropriate mol% of PBD as a comonomer in Bisphenol-A-based copolycarbonates. The lowering of the T-g values of (co)polycarbonates can be attributed primarily to the packing disruptive effect of flexible pentadecyl chains. Furthermore, the effect of incorporation of PBD as a comonomer on water contact angle values of (co)polycarbonates is evaluated.
Keywords: aromatic polycarbonates; biobased bisphenol; Cashew nut shell liquid; pentadecyl chain; Renewable resources

Synthesis, characterization and UV-crosslinking of aromatic (Co)polycarbonates bearing pendant azido groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Talanikar, Aniket A.; Lochab, Bimlesh; Wadgaonkar, Prakash P. (ChemistrySelect, 2022)
A new series of (co)polycarbonates bearing pendent azido groups was synthesized by polycondensation of varying molar proportions of 4, 4'-(5-azidopentane-2, 2-diyl) diphenol and bisphenol-A with triphosgene. The chemical structures, compositions and random nature of (co)polycarbonates were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of (co)polycarbonates were in the range 0.63-0.77 dL g(-1) and 35,400-43,400 g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. (Co)polycarbonates could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polycarbonates were further characterized using IR spectroscopy, XRD, TGA and DSC. The thermal crosslinking of (co)polycarbonates bearing pendant azido groups was studied by DSC analysis. Independently, (co)polycarbonates bearing pendant azido groups were exposed to UV irradiation at wavelength of 254 nm and decomposition reaction of azido groups was monitored by FT-IR spectroscopy. The complete decomposition of azido groups was observed with exposure time of 30 min. The formed cross-linked (co)polycarbonates exhibited improved % char yield values compared to parent (co)polycarbonates. The measurement of mechanical properties of representative crosslinked (co)polycarbonates indicated increase in tensile strength and Young's modulus and decrease in % elongation compared to corresponding parent linear (co)polycarbonates.
Keywords: Aromatic polycarbonate; Pendant azido group; solution polycondensation; Triphosgene; UV-crosslinking